Protein-energy supplementation during pre-weaning on the performance and metabolism of crossbred female calves - David Jaimes Portilla; Román Maza Ortega; Deilen Paff Sotelo Moreno (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the effect of dietary supplementation with a protein-energy concentrate during the pre-weaning period on the nutritional and productive performance and on the metabolic response of crossbred female calves fed medium-quality forage in a dual-purpose system. Twelve Gyr×Holstein suckling female calves, with a body weight of 123.0±0.23 kg and an initial average age of 5.7±0.38 months, were distributed in a completely randomized design. Two treatments were carried out: animals without supplementation (control); and animals supplemented with 5.0 g kg-1 body weight of a protein-energy concentrate, containing 23.01% crude protein and 78% total digestible nutrients. Supplementation increased the intake of crude protein, nonfibrous carbohydrates, and neutral detergent fiber, but had no effect on dry matter intake. There was also an increase in the blood concentration of serum urea nitrogen. In addition, supplementation decreased forage intake time and increased idle time. The final body weight of the supplemented female calves was the heaviest, but did not influence the body measurements of the animals. Supplementation with 5.0 g kg-1 body weight of a protein-energy concentrate during the pre-weaning period improves the productive performance of crossbred female calves.